MODEL PENGEMBANGAN PERIKANAN TANGKAP BERBASIS MINAPOLITAN DI KABUPATEN GORONTALO UTARA - Alfi Sahri R. Baruadi; Domu Simbolon; Ari Purbayanto; Roza Yusfiandayani (Fakultas Perikanan dan Ilmu Kelautan, 2012)
Fishery resources at NorhGorontalo disrict was huge. The potential of Fishery Management Area from Laut Sulawesi to Pasicific Ocean includes around 590.970 ton of pelagicdivided into175.260 ton large pelagic, 384.750 ton small pelagic and the other kind of fish around 30.960 ton. On the other hand, the utilization of fishery resources still minimun that was only 46%. Government at North Gorontalo made capture fisheris as a main program to improve society welfare to minimize the lack of fishery resources utilization. The government should be aware of this situation to formulate and decide each policy. Policy that has been applied in this recent year in NorthGorontalo district was Minapolitan and it was held by the Indonesia Ministry of Marine and Fishery joined with Local Government. So, research of development fishery capture based minapolitan model was needed to designed a policy model as a guide to decide a capture fisheries policy. Methodology that using in this research was surplus production analysis to analyze the fish resource, proper tools to capture fish analysis, and SEM (Structure Equation Modeling) analysis. The result of this research showed that the utilization of fishery resources still lack under MSY (Maximum Sustainable Yield). Some of programs that should be developed were purse seine, hand line tuna,liftnet, hand line, and payang. The objective of minapolitan policy was creating local economic growth and increasing capture fisheries production and guarantee the quality of capture fisheries.